2019
DOI: 10.3390/met9101089
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Different Die Bearing Geometries on the Wire-Drawing Process

Abstract: Metalworking is an essential process for the manufacture of machinery and equipment components. The design of the die geometry is an essential aspect of metalworking, and directly affects the resultant product’s quality and cost. As a matter of fact, a comprehensive understanding of the die bearing geometry plays a vital role in the die design process. For the specific case of wire drawing, however, few efforts have been dedicated to the study of the geometry of the bearing zone. In this regard, the present pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
(25 reference statements)
4
8
0
Order By: Relevance
“…The change of bearing zone length in the region III leads to the variations of both surface and centre stresses, indicated by the nodes 580 and 40 respectively. Vega et al [34], Martínez et al [35], and other authors [2,22,24] have shown that the die angle, friction coefficient, and bearing zone length significantly affect the stress during the drawing process. We note that the above findings are consistent with previous studies.…”
Section: (A)mentioning
confidence: 99%
“…The change of bearing zone length in the region III leads to the variations of both surface and centre stresses, indicated by the nodes 580 and 40 respectively. Vega et al [34], Martínez et al [35], and other authors [2,22,24] have shown that the die angle, friction coefficient, and bearing zone length significantly affect the stress during the drawing process. We note that the above findings are consistent with previous studies.…”
Section: (A)mentioning
confidence: 99%
“…In this regard, the wires must have sufficient mechanical strength and withstand the effects of atmospheric phenomena and chemical impurities along with possessing good electrical conductivity. Therefore, in recent years, during the construction of power lines, much focus has been directed toward bimetallic materials formed by a combination of metals dissimilar in their layered structure [ 12 , 13 , 14 ]. The main quality indicators of bimetallic wire and rods are the combination of their strength and plastic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such simplification does not fully take into account the phenomena occurring in the material before entering the elastic–plastic deformation region inside of the drawing die, and the assumption that the material before entering the die reduction angle is stress-free is not true, as it is obvious that elastic–plastic deformations must be preceded by elastic deformations [ 24 ]. Among research works taking that into account, Martinez et al [ 25 , 26 ] investigated the influence of the wire drawing parameters throughout the process, as well as die geometry on generated heat, friction, and plastic deformations. They confirmed that as a result of the material flowing in the direction of the die axis, the stresses changed from compressive to tensile.…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations have been made when the drawing angle has been changed. The authors of these two works [ 25 , 26 ] did not notice any influence of the die geometry on the axial deformations. Skołyszewski et al [ 5 ], in their research work, investigated the influence of back tension throughout the wire drawing process of steel on recorded stress values and noted that despite the very short length of the region of elastic deformations, its values exceeded several times the value of the metal unit pressure on the wall of the drawing die, which is an extremely dangerous phenomenon during the wire drawing process.…”
Section: Introductionmentioning
confidence: 99%